Fermentation optimization of Mycobacterium smegmatis using experimental design - Wendel, Sebastian O.; Perera, Ayomi S.; Pfromm, Peter H.; Czermak, Peter; Bossmann, Stefan H. (My University, 2014)
The exceptionally stable mycobacterial protein porin A (MspA) from Mycobacterium smegmatis has potential applications in protein-based solar cells, and as a biotemplate for nano-wires and nano-dots. These applications would be enabled by an efficient and cost effective method to grow the host organism at high cell mass yields, and recover purified MspA. In this work, the cell mass yield was maximized and costs lowered by applying experimental design (varying nitrogen and iron contents according to a Doehlert matrix) based on a minimal fermentation medium that was reported earlier. Glucose use was minimized by adjusting glucose feed based on analyzing residual glucose after fermentation. The costs for extracted and purified MspA were lowered by 67% for the minimum medium and the optimized composition derived here compared to commercial medium (7H9 Middlebrook).
Keywords: Mycobacterium smegmatis; MspA; Medium optimization; Protein extraction